Preparation process of super hydrophobic nano coating after hexavalent chromium polishing of copper alloy

By using the preparation process of superhydrophobic nanocoating after the copper alloy conductive joints with hexavalent chromium polished copper alloy, the problems of corrosion of the conductive joints and uneven thickness of the hydrophobic protective film in corrosive environments are solved, and a hydrophobic nanocoating that is resistant to high temperature and salt spray is realized, ensuring conductive properties and corrosion resistance.

CN119753658APending Publication Date: 2025-04-04SHENZHEN TIANYUE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964547.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The conductive joints of copper alloys are prone to corrosion in corrosive environments, resulting in reduced conductivity, and the strong oxidation of hexavalent chromium polishing liquid will lead to uneven thickness of the hydrophobic protective film, resulting in problems such as chromatic aberration and spots.

Method used

The preparation process of superhydrophobic nanocoating after hexavalent chromium polishing copper alloy is adopted, including copper alloy surface oil removal, hexavalent chromium polishing, surface microetching, surface activation and protection, and finally a hydrophobic nanocoating that is resistant to high temperature and salt spray is formed through baking and drying.

Benefits of technology

The copper alloy surface is formed with high temperature and salt spray resistance, which ensures the conductive properties and corrosion resistance of the conductive joints, and avoids chromatic aberration and spot problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature resistant and hydrophobic nano coating process for a copper alloy surface. A nano-scale protective film is formed by self-assembly of mercapto alcohol with a hydrophobic chain on the copper alloy surface. The process flow can ensure the formation of a highly protective film that is resistant to high temperature and salt spray. The specific process flow is as follows: acidic degreasing and deoxidation of the copper alloy surface, hexavalent chromium polishing, surface microetching, surface adjustment and activation, and passivation protection. The copper alloy surface is rinsed three times with pure water between processes. The polishing time of hexavalent chromium is reduced to facilitate obtaining a bright and smooth polishing surface. After the copper alloy is polished, a transparent protective film is formed on the copper surface due to the strong oxidizing property of hexavalent chromium. Subsequently, trivalent iron microetching is performed, and the bright copper is easily oxidized and discolored. The surface of the copper alloy is adjusted again with an acidic surfactant to form a temporary protective layer on the surface that is easily replaced by active components in a passivation solution. Finally, after passivation protection, a salt spray and high-temperature resistant nano coating is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to metal passivation, and in particular to a preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing of a copper alloy. Background Art

[0002] Copper and copper alloys are widely used in mechanical instruments, electronic components, chemical industry, transportation industry, new energy, information and communication and other fields due to their excellent electrical conductivity, thermal conductivity, cold resistance, corrosion resistance and good plasticity, as well as their affinity, solubility, chemical combination and good stability with other elements.

[0003] In the field of electric vehicles, conductive joints play a vital role, and copper alloys are widely used in conductive joints due to their good electrical and thermal conductivity. As a conductive joint, the main function of copper alloy is to transmit current. Any protective measures should ensure that while protecting copper, it does not increase excessive contact resistance and ensure smooth transmission of current. Because copper alloys are easily oxidized when in contact with oxygen in the air, forming oxide layers such as copper oxide. This will increase contact resistance, reduce electrical conductivity, and may even cause the joint to overheat, affecting the safe operation of electric vehicles. In addition, electric vehicles may encounter various corrosive environments during operation, such as rain, moisture, chemicals, etc. These corrosive substances will corrode copper alloy conductive joints, destroy the surface structure of the joints, reduce electrical conductivity, and even cause joint failure.

[0004] Chromic acid and chromate are commonly used for the passivation of copper and copper alloys in industrial production. Although the process is relatively simple and mature, and the passivation effect is excellent, since only a very small amount of chromic acid is involved in film formation, a large amount of chromium-containing waste liquid is directly discharged into the environment. In aqueous solution, chromium mainly exists in two types: trivalent chromium and hexavalent chromium. Hexavalent chromium is extremely toxic. Frequent contact with hexavalent chromium ions will cause adverse reactions such as skin ulcers and organ damage.

[0005] After polishing the copper alloy, a transparent trivalent chromium hydrogel protective film will be formed on the copper surface due to the strong oxidizing property of the hexavalent chromium polishing liquid. Continuing the protection process will cause uneven thickness of the hydrophobic protective film, resulting in color difference, mottling and other problems. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing of copper alloy, so as to overcome the shortcomings of the prior art.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A preparation process of super hydrophobic nano coating after hexavalent chromium polishing of copper alloy, Step 1: Degreasing the copper alloy surface; use for 5% slotting, control the temperature at 25℃-80℃, and ultrasonic cleaning time for 2-10min.

[0008] Step 2: Hexavalent chromium polishing: Soak in hexavalent chromium polishing liquid at room temperature for 10s-60s.

[0009] Step 3: Surface microetching: Use trivalent iron system polishing liquid with a concentration of 20%-100%, soak for 10-120s, and control the temperature within the range of 25℃-40℃.

[0010] Step 4: Surface activation: Soak in 10% concentration of pickling activator at room temperature for 1-10 minutes.

[0011] Step 5: Protection: Soak in 10%-100% concentration conversion solution for 2-30 minutes, and control the temperature between 25-40℃.

[0012] Step 6: Bake and dry, use an air gun to blow away excess moisture, and place in an oven at 80-105℃ for 20-40 minutes.

[0013] Furthermore, between each step, a cleaning step is provided: cleaning: soaking in a flowing water tank for 1-3 minutes, soaking and cleaning three times in sequence, bubbling or stirring appropriately during the soaking process.

[0014] Furthermore, the acid washing activator components used in step 4 include: in terms of mass percentage, 61.0% water, 10.0% citric acid, 12.0% aminosulfonic acid, 5.00% glycerol, 3.0% hydrogenated castor oil polyoxyethylene ether-20, 2.0% Tween-20, 6.0% polyethylene glycol-600 and 0.2% phenoxyethanol.

[0015] Furthermore, the conversion liquid components used in step five include, by mass percentage, 76.6% water, 1.0% dodecanethiol, 6.0% hexadecanethiol, 1.0% aminosulfonic acid, 0.20% BTA, 0.2% hexadecyl hydroxyethyl imidazoline, 5.0% dipropylene glycol methyl ether and 10.0% APG-0810. Compared with the prior art, the present invention has the following beneficial effects: The invention provides a high-temperature resistant and hydrophobic nano coating process for the surface of a copper alloy. Mercapto alcohol with a hydrophobic chain is used to self-assemble on the surface of the copper alloy to form a nano-scale protective film. This process flow can ensure the formation of a highly protective film that is resistant to high temperatures and salt spray. The specific process flow is as follows: acidic degreasing and deoxidation of the copper alloy surface - hexavalent chromium polishing - surface micro-etching - surface adjustment and activation - passivation protection, and pure water is used for rinsing three times between the processes. The purpose of acidic degreasing and deoxidation is to remove oil, ash and oxide scale on the surface of copper alloy, reduce the polishing time of hexavalent chromium, and facilitate the acquisition of bright and smooth polished surface. After the copper alloy is polished, due to the strong oxidizing property of hexavalent chromium, a transparent protective film will be formed on the copper surface, so there is a process of removing chromium film on the surface of trivalent iron. The subsequent surface adjustment is because after micro-etching of trivalent iron, the bright copper is easy to oxidize and discolor. The surface of the copper alloy is adjusted again with an acidic surfactant to form a temporary protective film on the surface that is easily replaced by the active components in the passivation solution. Finally, after passivation protection, a salt spray and high temperature resistant nano coating is obtained.

[0016] The above-mentioned protective film that can be replaced is a non-ionic surfactant layer formed by the hydrogen bonding force between polyoxyethylene ether and the copper surface. It can be replaced by the passivation solution (that is, the conversion solution) and then attached to the copper alloy, forming the final high temperature resistant and salt spray resistant hydrophobic nano coating on the copper surface while ensuring that the copper does not oxidize and discolor. DETAILED DESCRIPTION

[0017] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0019] The present invention is described in detail below in conjunction with various embodiments: In this embodiment, a preparation process of a super-hydrophobic nano-coating after hexavalent chromium polishing of copper alloy is provided. Step 1: Degreasing the copper alloy surface; use for 5% slotting, control the temperature at 25℃-80℃, and ultrasonic cleaning time for 2-10min.

[0020] Step 2: Hexavalent chromium polishing: Soak in hexavalent chromium polishing liquid at room temperature for 10s-60s.

[0021] Step 3: Surface microetching: Use trivalent iron system polishing liquid with a concentration of 20%-100%, soak for 10-120s, and control the temperature within the range of 25℃-40℃.

[0022] Step 4: Surface activation: Soak in 10% pickling activator at room temperature for 1-10 minutes.

[0023] Step 5: Protection: Soak in 10%-100% concentration conversion solution for 2-30 minutes, and control the temperature between 25-40℃.

[0024] Step 6: Bake and dry. Use an air gun to blow away excess moisture and place in an oven at 80-105℃ for 20-40 minutes.

[0025] Furthermore, between each step, a cleaning step is provided: cleaning: soaking in a flowing water tank for 1-3 minutes, soaking and cleaning three times in sequence, bubbling or stirring appropriately during the soaking process.

[0026] Furthermore, the acid washing activator components used in step 4 include: in terms of mass percentage, 61.0% water, 10.0% citric acid, 12.0% aminosulfonic acid, 5.0% glycerol, 3.0% hydrogenated castor oil polyoxyethylene ether-20, 2.0% Tween-20, 6.0% polyethylene glycol-600 and 0.2% phenoxyethanol.

[0027] Furthermore, the conversion liquid components used in step five include, by mass percentage, 76.6% water, 1.0% dodecanethiol, 6.0% hexadecanethiol, 1.0% aminosulfonic acid, 0.20% BTA, 0.2% hexadecyl hydroxyethyl imidazoline, 5.0% dipropylene glycol methyl ether and 10.0% APG-0810. Example

[0028] Step 1: Degreasing the copper alloy surface; use 5% slotting, control the temperature at 65℃, and ultrasonic cleaning time for 5 minutes.

[0029] Then wash; Wash: Soak in running tap water for 2 minutes, and wash three times in sequence. Bubble or stir appropriately during the soaking process. The cleaning method of the cleaning steps mentioned below is the same as here, and will not be repeated below. After cleaning, proceed to the next step.

[0030] Step 2: Hexavalent chromium polishing: Soak in hexavalent chromium polishing liquid at room temperature for 20 seconds. Then clean, and proceed to the next step after cleaning.

[0031] Step 3: Surface microetching; use trivalent iron system polishing liquid with a concentration of 50%, soak for 1.0min, and control the temperature within the range of 25℃-30℃. Then clean, and proceed to the next step after cleaning. After the hexavalent chromium is polished, a colorless and transparent trivalent chromium hydrogel film will be formed on the copper alloy surface. This step can dissolve the trivalent chromium hydrogel film.

[0032] Step 4: Surface activation; soak in 10% acidic activator at room temperature for 2 minutes. Then wash, and proceed to the next step after washing. Specifically, the acid activator components used in step 4 include: by mass percentage, 61.0% water, 10.0% citric acid, 12.0% aminosulfonic acid, 5.0% glycerol, 3.0% hydrogenated castor oil polyoxyethylene ether-20, 2.0% Tween-20, 6.0% polyethylene glycol-600 and 0.2% phenoxyethanol. After micro-etching with trivalent iron, bright copper is easily oxidized and discolored. The surface of the copper alloy is adjusted again with an acidic surfactant to form a temporary protective film on its surface that is easily replaced by the active components in the passivation solution. This can prevent copper oxidation and discoloration, and will not cause uneven thickness when the subsequent passivation film is formed.

[0033] Step 5: Protection: Soak in 10% concentration conversion solution for 30 minutes, and control the temperature between 25-30℃. Then clean, and proceed to the next step after cleaning. The conversion solution used in step 5 includes: by mass percentage, 76.6% water, 1.0% dodecanethiol, 6.0% hexamethylenethiol, 1.0% aminosulfonic acid, 0.20% BTA, 0.2% hexadecyl hydroxyethyl imidazoline, 5.0% dipropylene glycol methyl ether and 10.0% APG-0810.

[0034] In this step, the protective film can be replaced by the conversion liquid to directly form a new layer of high temperature and salt spray resistant hydrophobic nano coating on the copper.

[0035] Step 6: Bake and dry. Use an air gun to blow away excess moisture and place in an oven at 100-105℃ for 30 minutes.

[0036] According to the above steps, a layer of hydrophobic nano coating resistant to high temperature and salt spray is obtained on the surface of the copper alloy. Specifically, it can withstand baking at 150°C for 1 hour without changing color, and can withstand neutral salt spray for 48 hours. Example

[0037] Step 1: Degreasing the copper alloy surface; use 5% slotting, control the temperature at 60℃, and ultrasonic cleaning time for 10 minutes.

[0038] Then wash; Wash: Soak in running tap water for 2 minutes, and wash three times in sequence. Bubble or stir appropriately during the soaking process. The cleaning method of the cleaning steps mentioned below is the same as here, and will not be repeated below. After cleaning, proceed to the next step.

[0039] Step 2: Hexavalent chromium polishing: Soak in hexavalent chromium polishing liquid at room temperature for 60 seconds. Then clean, and proceed to the next step after cleaning.

[0040] Step 3: Surface microetching; use trivalent iron system polishing liquid with a concentration of 100%, soak for 1.0min, and control the temperature within 25±1.0℃. Then clean, and proceed to the next step after cleaning. After the hexavalent chromium is polished, a colorless and transparent trivalent chromium hydrogel film will be formed on the copper alloy surface. This step can dissolve the trivalent chromium hydrogel film.

[0041] Step 4: Surface activation; soak in 10% acidic activator at room temperature for 10 minutes. Then wash, and proceed to the next step after washing. Specifically, the components of the pickling activator used in step 4 include: by mass percentage, 61.0% water, 10.0% citric acid, 12.0% aminosulfonic acid, 5.00% glycerol, 3.0% hydrogenated castor oil polyoxyethylene ether-20, 2.0% Tween-20, 6.0% polyethylene glycol-600 and 0.2% phenoxyethanol. After micro-etching with trivalent iron, bright copper is easily oxidized and discolored. The surface of the copper alloy is adjusted again with an acidic surfactant to form a temporary protective film on its surface that is easily replaced by the active components in the passivation solution. This can prevent copper oxidation and discoloration, and will not cause uneven thickness when the subsequent passivation film is formed.

[0042] Step 5: Protection: Soak in 50% concentration conversion solution for 10 minutes, and control the temperature between 30-35°C. Then wash, and proceed to the next step after washing. The conversion solution used in step 5 includes: by mass percentage, 76.6% water, 1.0% dodecanethiol, 6.0% hexamethylenethiol, 1.0% aminosulfonic acid, 0.20% BTA, 0.2% hexadecyl hydroxyethyl imidazoline, 5.0% dipropylene glycol methyl ether and 10.0% APG-0810.

[0043] In this step, the protective film can be replaced by the conversion liquid to directly form a new layer of high temperature and salt spray resistant hydrophobic nano coating on the copper.

[0044] Step 6: Bake and dry. Use an air gun to blow away excess moisture and place in an oven at 80-85℃ for 40 minutes.

[0045] According to the above steps, a layer of high temperature and salt spray resistant hydrophobic nano coating is obtained on the surface of the copper alloy. Specifically, it can withstand baking at 200°C for 10 minutes without changing color, and can withstand neutral salt spray for 72 hours.

[0046] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, all possible combinations of the technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered as within the scope of this specification. For ordinary technicians in this field, they can make several modifications and improvements without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing of copper alloy, characterized in that: Step 1: Degreasing the copper alloy surface; 5% slotting, temperature control at 25℃-80℃, ultrasonic cleaning time 2-10min, Step 2: Hexavalent chromium polishing: Soak in hexavalent chromium polishing liquid at room temperature for 10s-60s. Step 3: Surface microetching: Use trivalent iron system polishing liquid with a concentration of 20%-100%, soak for 10s-120s, and control the temperature within the range of 25℃-40℃. Step 4: Surface activation: Soak in 10% pickling activator at room temperature for 1-10 minutes. Step 5: Protection: Soak in 10%-100% concentration conversion solution for 2-30 minutes, and control the temperature between 25-40℃. Step 6: Bake and dry. Use an air gun to blow away excess moisture and place in an oven at 80-105℃ for 20-40 minutes.

2. The preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing copper alloy as claimed in claim 1, characterized in that: Between each step, a cleaning step is set - Cleaning: Soak in a running water tank for 1-3 minutes, soak and clean three times in sequence, and bubble or stir appropriately during the soaking process.

3. The preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing copper alloy as claimed in claim 1, characterized in that: The acid washing activator components used in step 4 include: in terms of mass percentage, 61.0% water, 10.0% citric acid, 12.0% aminosulfonic acid, 5.0% glycerol, 3.0% hydrogenated castor oil polyoxyethylene ether-20, 2.0% Tween-20, 6.0% polyethylene glycol-600 and 0.2% phenoxyethanol.

4. The preparation process of a super-hydrophobic nano coating after hexavalent chromium polishing copper alloy as claimed in claim 1, characterized in that: The conversion liquid components used in step 5 include, by mass percentage, 76.6% water, 1.0% dodecanethiol, 6.0% hexadecanethiol, 1.0% aminosulfonic acid, 0.20% BTA, 0.2% hexadecyl hydroxyethyl imidazoline, 5.0% dipropylene glycol methyl ether and 10.0% APG-0810.